2017
DOI: 10.1080/16549716.2017.1347369
|View full text |Cite
|
Sign up to set email alerts
|

‘I am all alone’: factors influencing the provision of termination of pregnancy services in two South African provinces

Abstract: Background: Globally, universal access to sexual and reproductive health care services has been re-emphasised. One-third of maternal deaths could be averted by improving access to safe abortion services. Anecdotal evidence suggests that the implementation of the Choice of Termination of Pregnancy Act has been suboptimal in South Africa. Objectives: In two South African provinces, determine: the proportion of designated termination of pregnancy (TOP) facilities that provide these services; explore the factors t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 32 publications
0
38
2
Order By: Relevance
“…We did not measure stigma in the survey, and this could explain the difference in findings. However, the findings in the quantitative study contradict those in the qualitative study among a sample of TOP provides who reported on the feelings of loneliness and the courtesy stigma experienced by these providers …”
Section: Discussioncontrasting
confidence: 85%
See 4 more Smart Citations
“…We did not measure stigma in the survey, and this could explain the difference in findings. However, the findings in the quantitative study contradict those in the qualitative study among a sample of TOP provides who reported on the feelings of loneliness and the courtesy stigma experienced by these providers …”
Section: Discussioncontrasting
confidence: 85%
“…We obtained a 2014 list of these designated TOP facilities from the national department of health, which was compared with the provincial data base from each of the study provinces. The details of these TOP facilities are described elsewhere …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations